2022
DOI: 10.1021/acsagscitech.1c00239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alternate Wetting and Drying Irrigation Practice on Rice Crop Growth and Yield: A Lysimeter Study

Abstract: Alternate wetting and drying irrigation practice in rice cultivation can save a significant amount of irrigation water. It involves irrigating rice fields alternately based on an irrigation triggering criterion and possibly influences the soil–plant–water system. In this study, field experiments were carried out for 3 years with three levels of soil matric potential heads (SMPHs) (no soil water stress: conventional irrigation, NS; 400 cm: mild soil water stress, MS; and 750 cm: severe soil water stress, SS) al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In India, Shekhar et al [31] conducted alternate wetting and drying field research involving three levels of soil moisture depletion with sub-treatments involving nitrogen management. Yields for conventional irrigation with alternate wetting and drying imposing only mild stress were statistically equivalent.…”
Section: Intermittent Flood or Alternate Wetting And Dryingmentioning
confidence: 99%
“…In India, Shekhar et al [31] conducted alternate wetting and drying field research involving three levels of soil moisture depletion with sub-treatments involving nitrogen management. Yields for conventional irrigation with alternate wetting and drying imposing only mild stress were statistically equivalent.…”
Section: Intermittent Flood or Alternate Wetting And Dryingmentioning
confidence: 99%
“…Previous studies have shown that compared to continuous flooding, all water-saving practices allow for sustainable rice production [127]. According to research [126][127][128][129][130], there are multiple water-saving technologies, including alternate wetting and drying (AWD), soil water potential (SWP), non-flooded mulching cultivation, aerobic rice system (ARS), efficient irrigation regime (EIR), saturated soil culture (SSC), field water level (FWL), intermittent drainage (ID), leaching and flushing methods (LFM), conventional flooding-midseason drainage-flooding irrigation (FDF), etc. The most popular water-saving technologies developed for rice production systems is the alternate wetting and drying (AWD) [121,123].…”
Section: Water-saving Irrigation Practices For Rice Productionmentioning
confidence: 99%
“…Water-use efficiency (WUE) is expressed as the ratio of total biomass to evapotranspiration or as the ratio of grain yield to water received from irrigation and rain [19][20][21]3]. It is described as the ability of a plant to absorb concentrations of carbon and prevent excessive water loss by controlling stomatal closure.…”
Section: Water Use Efficiency and Transpiration Efficiencymentioning
confidence: 99%